CFD Simulation of Multi-phase Flow Inside the Hydro-viscous Speed Regulating Clutch - Guo Guangchao; Xing Zuohui (Jixie chuandong)
Based on the computational fluid dynamics theory,the mathematical model of the fluid domain inside the hydro-viscous speed regulating clutch is established,and the multi-phase flow field in the radial groove friction pair is solved numerically by the CFD software. The influence of the groove number and speed on the oil film pressure distribution under cavitation effect is studied,and the change of load-carrying capacity along with particle mass fraction and diameter is analyzed by the method of phase coupling. The result indicates that the pressure increases with the increase of the speed,and shows the periodicity and inhomogeneity,in which the pressure decreases gradually along the direction of the radius increase and tends to be consistent,and the groove number has little effect on the maximum pressure. In the transitional region,the pressure fluctuates obviously,and the negative pressure appears at the edge of the groove,the most significant cavitation effect occurs in the inner wall of the groove opposite to the direction of rotation. With the increase of the particles mass fraction,the load-carrying capacity increases,and compared with the minimum film thickness,the particle diameter is too large or too small,its influence on load-carrying capacity is not significant,when the particle size exceeds a certain value,the load-carrying capacity will be significantly improved.